Cost and Time Efficiency Analysis of Manual and e-Procurement Systems in Roads and Highways Department: Tender Advertising Issue Perspective (British Journal of Multidisciplinary and Advanced Studies, 2024)
Public procurement is a vital process to procure goods, works and services, ensuring accountability that ensures cost and time-savings. Roads and Highways Departments (RHD) is a big department chosen as a target population for this study. All RHD Procurement Entities (PE) use manual and e-procurement tendering systems. However, cost and time reduction is a considerable barrier to RHD procurement. The manual tendering procedure is costly and time-consuming since it requires big-size tender advertisements in print media like daily papers. In RHD, however, no comparative analysis of the efficiency in the cost and time context of tender advertising has been explored. Therefore, using a stratified sampling method, the RHD's e-Procurement-related PE officers were chosen as a sample. The mean value of advertisement cost and time of the e-tender system and the manual tender system as a continuous normally distributed variable was utilized to compare two groups using the independent samples t-test model. The study's novel contribution is the comparison of efficiency in terms of cost and time context between two sets of manual and e-tender advertisements. According to the survey results, the e-procurement system showed lower cost and time involved in the tender advertising comparing manual tender. The results will also aid academicians and students and improvements to e-GP policy standards.